The Mameluke and Mongolian Struggle and its Effects on the history of the Near East - Arslantaş, Yüksel (Türk Tarih Kurumu [EN], 2003)
The 13th century was a chaotic period in the Turkish-Islamic world. The Mongols had begun to appear in the Middle East and were posing a threat to Anatolia, Azerbaijan, Iraq, Syria, and Egypt. After the Mamelukes defeated the Ayyubides in 1250 and occupied their lands, they waged a successful battle against the Mongols who were then threatening Syria and managed to halt their progression there. In this way the Mamelukes broke the power of this destructive force that could have invaded Egypt, the Mediterranean and even Europe. The struggle between the Mamelukes and the Mongols continued until the beginning of the 14th century, with the Mamelukes the ultimate victor who succeeded in ending the Mongolian invasion. The Mongolian invasion had political, economic, and social ramifications in the Middle East. The invasions gave rise to local uprisings with resultant damage to crops and cities. In addition, the large armies formed to resist the Mongols also served to damage the Mameluke economy.

XIII. asır, Orta Doğu'nun siyasi haritasında yeni şekillenmelerin ve güç dengelerinin ortaya çıktığı, Türk-İslam âleminin karışık bir asrıdır. Bu yüzyıla girerken Eyyûbi Devleti'nin en güçlü sultanı Selahaddin-i Eyyûbi'nin (1174-1193) ölümüyle halefleri arasında taht mücadeleleri başlamış, bu mücadelelerden galip çıkan bazı Eyyûbi emir ve beyleri otoritelerini tesis ettikten sonra zaman zaman Kuzey Suriye'de Türkiye Selçuklu Devleti ile hakimiyet mücadelesine girişmişlerdir. Bu durum 1250 yılında Eyyûbi hükümdarı Melik Salih Necmeddin'in (1240-1250) ölümüne kadar devam etmiş, onun ölümünden sonra başlayan karışıklıklar son Eyyûbi hükümdarı El-Melikü'l-Muazzam Turanşah'ın Memlûkler tarafından öldürülmesi ve Memlûk Devleti'nin kurulmasıyla son bulmuştur (1250)(1).
Memlûk-Moğol Mücadelesi ve Orta Doğu Tarihine Etkileri